The Routledge handbook of phenomenology of agency - Erhard, Christopher 1980-; Keiling, Tobias 1983- (Routledge, 2021)
"Phenomenology has primarily been concerned with questions about knowledge and ontology. However, in recent years the rise of interest and research in phenomenology and embodiment, the emotions and cognitive science has seen the concept of agency move to a central place in the study of phenomenology generally. The Routledge Handbook of Phenomenology of Agency is an outstanding reference source to this topic and the first volume of its kind. It comprises twenty-seven chapters written by leading international contributors. Organised into two parts, the following key topics are covered: major figures the metaphysics of agency rationality voluntary and involuntary action moral experience deliberation and choice phenomenology of agency and the cognitive sciences phenomenology of freedom embodied agency. Essential reading for students and researchers in phenomenology, philosophy of mind, metaphysics and philosophy of cognitive science The Routledge Handbook of Phenomenology of Agency will also be of interest to those in closely related subjects such as sociology and psychology"
Includes bibliographical references and index
Keywords: Phänomenologie; Rationales Denken; Gefühl; Willensfreiheit; Agent (Philosophy); Phenomenology; Aufsatzsammlung